Yo estaré contigo y te bendeciré : aproximación al concepto de bendición en el Antiguo Testamento - Judell, Patricia Hilda Pizzorno (2009)
The present work intends to investigate the concept of blessing in the Old Testament, especially in the Pentateuch. The first part analyzes the general characteristics of the term to bless / blessing in the Hebrew Bible and looks at the etymology, the semantic field, the formulas, the gestures, rites and words of blessing. As blessing is the continuous and permanent activity of God in history, the chapter finishes with the concept of history in the ancient world. The second chapter makes an incursion into the characteristics of the ancient biblical society in the two big periods of pre-state Israel and Israel as a state. It studies the nomadic pre-history and the pre-state sedentary Israel paying particular attention to the social organization in families, clans and tribes. In the state period, it gives attention to the Deuteronomic reform and its consequences in the social and religious life of Israel. The third chapter presents the exegesis of selected texts. In the primeval history it looks at blessing in creation, and in the patriarchal history it searches for the strokes of blessing in the family and state context. It also deals with the priestly blessing in Numbers 6,22-27 with special attention to the cult, and with selected texts from Deuteronomy that connect blessing with covenant and endow it with conditionality. The last chapter presents a reflection about family religion and state religion in Israel, and studies the characteristics of blessing in both fields that interrelate not always without tensions- and articulate between them.